2007
DOI: 10.1007/s00253-006-0774-y
|View full text |Cite
|
Sign up to set email alerts
|

Rare carotenoids, (3R)-saproxanthin and (3R,2′S)-myxol, isolated from novel marine bacteria (Flavobacteriaceae) and their antioxidative activities

Abstract: We isolated three orange or yellow pigment-producing marine bacteria, strains 04OKA-13-27 (MBIC08261), 04OKA-17-12 (MBIC08260), and YM6-073 (MBIC06409), off the coast of Okinawa Prefecture in Japan. These strains were classified as novel species of the family Flavobacteriaceae based on their 16S rRNA gene sequence. They were cultured, and the major carotenoids produced were purified by chromatographic methods. Their structures were determined by spectral data to be (3R)-saproxanthin (strain 04OKA-13-27), (3R,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 33 publications
3
92
0
2
Order By: Relevance
“…[7][8][9] These studies have reported the isolation of rare carotenoids, (3R)-saproxanthin and myxol, from Flavobacteriaceae, 7 and novel glyco-C 30 carotenoids (diapolycopenedioic acid xylosyl esters A, B, and C from Rubritalea squalenifaciens 8 and methyl glucosyl-3,4-dehydroapo-8¢-lycopenoate from Planococcus maritimus 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] These studies have reported the isolation of rare carotenoids, (3R)-saproxanthin and myxol, from Flavobacteriaceae, 7 and novel glyco-C 30 carotenoids (diapolycopenedioic acid xylosyl esters A, B, and C from Rubritalea squalenifaciens 8 and methyl glucosyl-3,4-dehydroapo-8¢-lycopenoate from Planococcus maritimus 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, diseased corals and sponges host a much greater abundance of Bacteroidetes than their healthy counterparts (Frias-Lopez et al, 2002;Pantos and Bythell, 2006;Webster et al, 2008b). The closest relative to the Bacteroidetes sequence that became highly abundant at 32 1C was a novel marine Flavobacteria with anti-oxidative properties (Shindo et al, 2007). The Bacteroidetes are diverse and abundant in the marine ecosystem (O'Sullivan et al, 2006) and are major utilizers of high-molecular mass dissolved organic matter (Cottrell and Kirchman, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have initiated the analysis of novel or rare types of carotenoids from a new colored marine bacterium, which was classified as belonging to a new species by 16S rRNA analyses [7]. Rubritalea squalenifaciens (strain HOact23 T ; MBIC08254 T ) is a rare marine bacterium belonging to subdivision 1 of Verrucomicrobia, a Gramnegative, heterotrophic mesophile, which was isolated from the marine sponge Halichondria okdai.…”
Section: Introductionmentioning
confidence: 99%